IMPLEMENTATION OF DRIVING SCHOOLS IN FORMING PANCASILA STUDENT PROFILES - Alin Gustiana; Dinar Sugiana Fitrayadi; Febrian Alwan Bahrudin (Journal Civics And Social Studies, 2023)
The purpose of this study was to find out the Implementation of the Driving School in Forming Pancasila–based Student Profiles. This research was conducted in the Driving School program at SMP Negeri 1 Karangtanjung, Pandeglang Regency. This research is a qualitative research using descriptive method of collecting data using observation, interview and documentation techniques. The results showed that the strategy used by the Driving School in forming the Pancasila-based Student Profiles was by conducting two different but interrelated learning, namely intra or general learning and thematic project learning. In addition, school principal has an important role in the process of forming the Pancasila-based Student Profiles and developing the teachers’ competencies. The obstacles faced by the school principal, teachers and students can be overcome by coordination and cooperation with the government, both among the teachers, and the students can be overcome by coordination and cooperation among the government, the teachers, the parents of students, the expert companions, and public education office.